The Effects of High Fat Diet on the Liver of the White Rat Model Obesity - Rusdiana, Rusdiana; Syarifah, Siti; Pane, Yunita Sari; Widjaja, Sry Suryani; Anggraini, Dwi Rita (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Nonalcoholic fatty liver disease (NAFLD) is the most common form of chronic liver disease with the manifestation of over-accumulation of fat in the liver. AIM: The purpose of this study was to assess the degree of occurrence of steatosis in rats induced by a standard diet, a high-fat diet, and a modified high-fat diet. METHODS: This study used 18 white rats of the Wistar strain, divided into three groups, and fed for 9 weeks. Before feeding, all rats were measured their body weight, abdominal circumference, and body length. We measured body weight every week, while body length and waist circumference were measured every 2 weeks. After 9 weeks of diet, all rats were subjected to injection of Ketamine and examined for metabolic markers and histopathological examination of liver organs. RESULT: There was an increase in body weight of rats in the three groups with the average percentage increase in body weight in the three groups of rats before and after being fed a diet for 9 weeks found in Group 1 29.19% 1 (187−264.40 g), Group 2 by 19.12% (219.33−275 g), and Group 3 24.53% (213.33−275 g). Steatosis in Group 1 was 57.50% of hepatocytes containing macrovesicular fat droplets and called Grade 2 (moderate). In contrast, with a high-fat diet, steatosis occurred around 93.33%−95% of hepatocytes containing macrovesicular fat droplets and called steatosis Grade 3 (severe). CONCLUSION: The percentage of hepatocytes that had steatosis in obese rats induced by a high-fat diet was more significant than in obese models induced by a standard diet.